Pre-Service Preschool Teachers' Attitudes towards Integrative Approach to the Development of Mathematical Thinking - Jasmina V. Milinković; Marija M. Vorkapić (University of Belgrade, Teacher Education Faculty, 2021)
The research deals with integrative approach in preschool education. The integrative approach is based on the hollistic perception of the preschool children's world. This approach is one of the key elements of the new concept of preschool education set out in a document entitled "Years of Ascent". The paper looks at the place of mathematical contents in the curriculum as well as the characteristics of the integrative approach which provide the conditions for the initial development of mathematical reasoning. The empirical section of the paper offers the results of the research related to pre-service preschool teachers' attitudes towards the integrative approach. The aim of the paper is to contribute, both theoretically and empirically, to a better understanding of the importance of the preschool teachers' professional competence to implement integrated activities.